Treatment of hollow glass bubbles with silane coupling agent. Sem on hollow glass bubbles, before and after treatment with silane coupling agent - Perdum, Andrei-Ionut (Technium BioChemMed, 2021)
In this study will be presented, how 20 millilitres of Silane Coupling Agent, adhered on 5 grams of Hollow Glass Bubbles (HGB), how the micro bubbles are looking before and after mixing, how to filter the hollow spheres from the agent and what needed to be taken in consideration when using coupling agents in processes. This paper will show how Silane Coupling Agent (3-Aminopropyl) triethoxysilane, adhered on the Hollow Glass Bubble (HGB). It is expected to observe at HR-SEM (High- Resolution Scanning Electron Microscopy) how the Hollow Glass Bubbles looks when the Silane Coupling Agent (KH-550) is applied on the filler vs when is not. During the process will be concluded, what risks should be taken in consideration, when using Silane Coupling Agents on Hollow Glass Spheres and what important information/ steps are needed to be taken in consideration before and after coupling treatment.